Impact of underfill and other physical dimensions on Silicon Lateral IGBT package reliability using computer model with discrete and continuous design variables - Rajaguru, P.; Lu, H.; Bailey, C.; Castellazzi, A.; Pathirana, V.; Udugampola, N.; Udrea, F. (Elsevier, 2018)
An effort to design and build a prototype LED driver system which is energy efficient, highly compact and with few component count was initiated by a consortium UK universities. The prototype system will be based on Silicon Lateral IGBT (LIGBT) device combined with chip on board technology. Part ofthis effort, finite element modelling and analysis were undertaken in order to mitigate the underfill dielectric breakdown failure and solder interconnect fatigue failure of the LIGBT package structure. Electro-static analysis was undertaken to predict the extreme electric field distribution in the underfill. Based on electro-static analysis, five commercial underfill were selected for thermo-mechanical finite element analysis on solder joint fatigue failure prediction under cyclic loading. A design optimisation analysis was endeavoured to maximise the solder interconnect reliability by utilising a computer model with continuous variable (physical dimensions) and discrete variables (underfill type) and a stochastic optimiser such as multi-objective mixed discrete particle swarm optimisation. From the optimisation analysis best trade off solution are obtained.